PENGARUH PENERAPAN STRATEGI PROBLEM SOLVING DALAM PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK SMP NEGERI DI PEKANBARU - Kaslini, Aishah Permata; Kartini, Kartini; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is the low ability of mathematical problem solving. The aim of this research is to know whether the implementation of problem solving strategy on cooperative learning Student Teams Achievement Divisions (STAD) type give a good influence towards the enhancement of mathematical problem solving ability to all students of SMP Negeri in Pekanbaru. This research is quasi-experiment and the design which used is nonequivalent control group. The population of this research was all students of SMP Negeri in Pekanbaru academic year 2017/2018. The samples were determined by purposive sampling technique, that two classes were selected, which were VIII.9 as the experimental class and VIII.8 as the control class. The experimental class was implemented by using problem solving strategy on cooperative learning STAD type and the control class was implemented by using conventional learning process. The data of this research was the enhancement of mathematical problem solving ability which obtained by the data of KPMM test before the treatment is given (pre-test) and the data of KPMM test after the treatment is given (post-test). The data was collected by giving a written test and it was analyzed by using one of statistical testing of hypothesis, which was Independent Samples t-Test. The result of statisctical testing of hypotesis shows that the implementation of problem solving strategy on cooperative learning Student Teams Achievement Divisions (STAD) type give a good influence towards the enhancement of mathematical problem solving ability to all students of SMP Negeri in Pekanbaru.Key Words: Problem Solving Strategy, Cooperative Learning STAD Type, Mathematical Problem Solving Ability.